2022
DOI: 10.1039/d1sc07267f
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenaelectro-catalyzed C–H acyloxylation for late-stage tyrosine and oligopeptide diversification

Abstract: Ruthenaelectro(II/IV)-catalyzed intermolecular C–H acyloxylations of phenols have been developed by guidance of experimental, CV and computational insights. The use of electricity bypassed the need for stoichiometric chemical oxidants. The sustainable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…To evaluate the feasibility of our oxygenation manifold, we first selected the fully protected tyrosine derivative 1 a housing a removable 2‐pyridyloxy group as DG [12b–c,e,14] . After evaluation of the reaction conditions, [15] we observed that the desired acetoxylation event could occur to provide mixtures of mono‐ and diacetoxylated compounds 2 a and 2 a’ , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the feasibility of our oxygenation manifold, we first selected the fully protected tyrosine derivative 1 a housing a removable 2‐pyridyloxy group as DG [12b–c,e,14] . After evaluation of the reaction conditions, [15] we observed that the desired acetoxylation event could occur to provide mixtures of mono‐ and diacetoxylated compounds 2 a and 2 a’ , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although the removal of the OPy group has been successfully accomplished in simple aryl systems upon treatment with methyl triflate followed by an alcoholic solution of sodium, its application in a peptide setting ushered in mixtures of various products. Notably, the cleavage of the DG was efficiently performed through a methylation/hydrogenation sequence [12b] to easily produce peptides housing a diphenol unit derived from a concomitant hydrolysis of the acetyl group. In this manner, L–DOPA ( 5 a ) and its peptidomimetics derivatives ( 5 b – c ) could be prepared in a reliable manner in up to 60 % yields (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…To our surprise, in sharp contrast with our experimental studies, the reaction pathway for substrate 1 ad was shown also energetically feasible; whereas the C−H activation and the reductive elimination steps were slightly more favored than for substrate 1 a , the oxidative addition of PIFA was shown more likely to happen with a substrate housing a weak coordinating group. Although merely speculative, we hypothesized that the transient ruthenacycle species with a strong pyridine unit as supporting ligand may be much more stable than the parent species featuring a considerably weak coordination mode, thereby resulting in the entire inhibition of the process and likely evolving into dimers or unproductive reaction pathways [26] . In fact, a control experiment with an equimolecular mixture of 1 a and 1 ad under the standard conditions exclusively delivered 2 a in 41% yield, thus evidencing a partial inhibition of the process in the presence of a pyridine unit.…”
Section: Resultsmentioning
confidence: 99%
“…6 Diverse bioconjugation technologies have been developed to achieve chemo-and site-selective functionalization of natural amino acids (AAs) for the purpose of selective protein modication. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The low abundance and unique reactivity of the thiol side chain of cysteine (Cys) make it an ideal candidate for bioconjugation chemistry. [21][22][23][24][25][26][27][28][29][30][31][32][33] Michaeltype addition, nucleophilic substitution and disulde exchange reaction represent the classical approaches for Cys-selective bioconjugation (Fig.…”
Section: Introductionmentioning
confidence: 99%